Correlation Between Improved Mating Efficiency and Weakened Scaffold-Kinase Interaction in the Mating Pheromone Response Pathway Revealed by Interspecies Complementation - Shi, Tianfang; Zeng, Junyuan; Zhou, Jungang; Yu, Yao; Lu, Hong (Frontiers in Microbiology, 2022)
Scaffold protein Ste5 and associated kinases, including Ste11, Ste7 and Fus3, are core components of the mating pheromone pathway, which is required to induce a mating response. Orthologues of these proteins are widely present in fungi, but to which extent one protein can be replaced by its orthologue is less well understood. Here, interspecies complementation was carried out to evaluate the functional homology of Ste5 and associated kinases in Kluyveromyces lactis, K. marxianus and Saccharomyces cerevisiae. These three species occupy important positions in the evolution of hemiascomycetes. Results indicated that Ste5 and associated kinases in K. lactis and K. marxianus could be functionally replaced by their orthologues to different extents. However, the extent of sequence identity, either between full-length proteins or between domains, did not necessarily indicate the extent of functional replaceability. For example, Ste5, the most unconserved protein in sequence, achieved the highest average functional replaceability. Notably, swapping Ste5 between K. lactis and K. marxianus significantly promoted mating in both species and the weakened interaction between the Ste5 and Ste7 might contribute to this phenotype. Consistently, chimeric Ste5 displaying a higher affinity for Ste7 decreased the mating efficiency, while chimeric Ste5 displaying a lower affinity for Ste7 improved the mating efficiency. Furthermore, the length of a negatively charged segment in the Ste7-binding domain of Ste5 was negatively correlated with the mating efficiency in K. lactis and K. marxianus. Extending the length of the segment in KlSte5 improved its interaction with Ste7 and that might contribute to the reduced mating efficiency. Our study suggested a novel role of Ste5-Ste7 interaction in the negative regulation of the pheromone pathway. Meanwhile, Ste5 mutants displaying improved mating efficiency facilitated the breeding and selection of Kluyveromyces strains for industrial applications.